Fungal Diversity In And Around Termite Mound, Mound Material Analysis, And Response Of Subterranean Termite, Globitermes Sulphureus (Haviland) (Blattodea: Termitidae) To Fungi - Guswenrivo, Ikhsan (2013)
Nowadays, many researchers are trying to develop biological control methods using fungi to control insect pests including termites. This study explored the termite-fungus relationship using Globitermes sulphureus (Haviland) as the model species. Isolation, purification and identification of fungi diversity in termite mounds of G. sulphureus werw carried out. These followed by introducing the fungus to termite and identified the termite interaction with the fungus. Further analysis of termite nest carton showed fungi diversity of G. sulphureus’ mound. Preliminary study found 24 species of fungus that were isolated and purified from ten different locations of G. sulphureus’ mound. Trichoderma sp., Aspergilus sp., and Penicillium sp. are the fungal that are commonly encountered in termite mounds. It is revealed that termite practice symbiont relationship with the five species of soil fungi that has been found with them. Lastly, the anti fungal test from G. sulphureus’ gut showed that they have anti fungal compound since it has the ability to inhibit the growth of fungus, shown by the formation of a clear zone surrounding the termite’s gut.